Insights into antimicrobial resistance among long distance migratory East Canadian High Arctic light-bellied Brent geese (Branta bernicla hrota) - Agnew, Austin; Wang, Juan; Fanning, Séamus; Bearhop, Stuart; McMahon, Barry J. (Irish Veterinary Journal, 2016)
Background: Antimicrobial resistance (AMR) is the most significant threat to global public health and ascertaining the role wild birds play in the epidemiology of resistance is critically important. This study investigated the prevalence of AMR Gram-negative bacteria among long-distance migratory East Canadian High Arctic (ECHA) light-bellied Brent geese found wintering on the east coast of Ireland. Findings: In this study a number of bacterial species were isolated from cloacal swabs taken from ECHA light-bellied Brent geese. Nucleotide sequence analysis identified five species of Gram-negative bacteria; the dominant isolated species were Pantoea spp. (n = 5) followed by Buttiauxella agrestis (n = 2). Antimicrobial susceptibility disk diffusion results identified four of the Pantoea spp. strains, and one of the Buttiauxella agrestis strains resistant to amoxicillin-clavulanic acid. Conclusion: To our knowledge this is the first record of AMR bacteria isolated from long distance migratory ECHA light-bellied Brent geese. This indicates that this species may act as reservoirs and potential disseminators of resistance genes into remote natural ecosystems across their migratory range. This population of geese frequently forage (and defecate) on public amenity areas during the winter months presenting a potential human health risk.